Optical Sensor Based on Dye Sensitized Solar Cell (DSSC) - Rahmadwati Rahmadwati; Sapriesty Nainy Sari; Eka Maulana; Akhmad Sabarudin (Institute of Advanced Engineering and Science, 2018)
An optical sensor is designed to convert a number of light energy in to electrical energy. The sensor hasbeen successfully measured using light illuminance to achieve electric parameters as the sensor output. In this research the optical sensor design was characterized according to the voltage and current output with the stimulus from mercury lamp. The sensor is customized from Dye-Sensitized Solar Cell with photo-electrode and photo-catalysator of Titanium Dioxide and extracted tobacco chlorophyll dye. Spin coating method was conducted to fabricate the thick layer deposition using selected material. Based on the absorbance measurement, it shows that tobacco dye has the characteristics of visible light absorption in the wavelength of 300-000 nm. The result of this research revealed that from 2 variation of optical sensor design square with active area of (2 cm x 2 cm) and (1 cm x 1 cm). Analitycal result shows that the sensor has wide linear characteristic in certain light illuminance both of output current and voltage.